Interação professor-bebê em creches inclusivas. - Joaquim, Cristiani da Silva (Universidade Federal de São Carlos, 2004)
The grouth on the importance of the Child Education, since its insertion into the Brazilian Constitution of 1988, brings an increase in the demand for this service and the fight for an inclusive education for young children. In this context, the purpose of this study was to describe the interactions between the day care center teacher and babies in an inclusive day care center that attended both babies with typical and atypical development. Two teachers and their students (age 12-36 months old), with typical and atypical development, were observed. The babies developmental repertoire was assessed by the Child Development Screening Tool Denver II (1989) and the Portage Guide to Early Education (Brazilian s version). The classroom activities of teachers and babies were videotaped through one week, during the regular time of work in the day care center. The record was transcripted in protocols previously developed, and latterly, submitted to a comparative analysis. Results showed that, in general, there was not a great difference in patterns of interaction established between teacher typical development babies and teacher atypical development babies. Both teachers seemed to be efficient in the children s participation during the activities. However, the kind of activity and the babies age seemed to be factors that influenced the teacher-child interaction. To younger babies, the activities in the classroom, with an established structure, seemed to involve both typical and atypical development babies, more than those freeplay activities. In relation to the older children, classroom activities were different in terms of proposed objectives. In the activities with the whole group, most of the typical development child was involved, but babies with atypical development were isolated from the playing. Issues related to formation and information of teachers from day care centers about child development and the factors related to their taking care in day care centers are discussed.
Keywords: Educação especial - inclusão; Educação de crianças; Interação adulto-criança; Inclusion; Child education; Adult-child interaction; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL